Scout Participation in Public Health Activities in the Jabodetabek Region in 2020 - P. A. Kodrat Pramudho; Armalia Reny (Journal for Quality in Public Health, 2020)
Health problems cannot be solved by health officials alone. The scout movement with millions of members throughout Indonesia clearly has a very important role in this. Scout members as millennial youth can be important agents of change, both for fellow youths, for parents and their families as well as for society as a whole. The members of the Ventura Scouts (16-20 years) andRover Scouts (20-25 years) in Indonesia number around 3.6 million (16% of 23 million). The study aims to observe the participation of the Ventura Scout and Rover Scouts who carry out various activities in the public health in the Jabodetabek area and which media cover/report on these Scouting activities. The research is qualitative in nature by observing news of Scout involvement in the public health activities in electronic mass media, print media and online media from January to June 2020. To complete the information, the researchers conducted in-depth interviews with several connected coaches and scouts. The analysis is carried out simply by comparing which media do the most news coverage/broadcasting about scout activities in the publicc health activities, and what motivations make scouts involved in public health activities. The research results showed that the of Ventura Scoutand Pandega Scouts were heavily involved in the public health activities, especially during the Covid19 pandemic, among others, distributing masks, becoming counselors, becoming role models. It turned out that online media was mostly followed by print and electronic media which covered and reported on the Ventura Scout and Rover Scout activities. This is also because the Ventura Scoutand Pandega Scouts are contributors to online media news, moreover Scouts have the tagline "Every Scout is a reporter". Meanwhile, the print and electronic media reported little about Scouting activities because they were more interesting in reporting on other youth groups. While the motivation of the Ventura Scoutsand Rover Scouts to be involved in public health activities because in accordance with Tri Satya and Dasa Darma Pramuka, among others, are helping others in life, participating in building the nation, loving nature and affection for fellow humans and being willing to help, and being responsible as citizens. The conclusion is that Scout involvement in the public health activities is quite often carried out in the Jabodetabek area in accordance with existing health problems in the local location. Scouts have been motivated to carry out humanitarian activities because of the pledge and promises contained in Tri Satya and Darma Pramuka. Online media reported the most on Scouting activities because the tagline "Every Scout is a reporter", while print media and electronic media reported the least on Scouting activities. The recommendation put forward is that every Scout carrying out activities in the health sector must be equipped with PPE (personal protective equipment), and the Scout Movement must continue to collaborate on an ongoing basis with the mass media, both printed, electronic and online.